2010
DOI: 10.1089/jop.2009.0098
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Concentrations of Bimatoprost Free Acid, Bimatoprost and Travoprost Free Acid in Cataract Surgical Patients Administered Multiple Topical Ocular Doses of LUMIGAN®or TRAVATAN®

Abstract: Once daily topical ocular administration of LUMIGAN or TRAVATAN for 3 weeks resulted in significant concentrations of BFA and TFA in the AH. Quantifiable levels of bimatoprost amide were also measured. Maximum concentrations of BFA (30.9 nM) and TFA (3.91 nM) in the anterior chamber are sufficient to fully activate the FP prostanoid receptors in the target cells of the ciliary muscle and trabecular meshwork. Both bimatoprost in LUMIGAN and travoprost in TRAVATAN are essentially prodrugs that are rapidly hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…In our study, bimatoprost rapidly hydrolyzed to bimatoprost acid in the AH and ICB of rabbit eyes, reaching concentrations well above the EC 50 values (103.4 ng/mL or 248.8 nM 2 hours postdose, and 68.21 ng/g or 164.4 nM 0.5 hour postdose, respectively), which is consistent with other published preclinical and clinical data supporting the role of bimatoprost acid for lowering IOP 11,35,36. ISV-215 formulation also increased bimatoprost levels in the AH and ICB (26.57 ng/mL or 64.02 nM and 65.05 ng/mL or 156.8 nM 0.5 hour postdose, respectively), reaching reported EC 50 values for human ciliary smooth-muscle cells, compared to results with just bimatoprost 0.03% alone.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, bimatoprost rapidly hydrolyzed to bimatoprost acid in the AH and ICB of rabbit eyes, reaching concentrations well above the EC 50 values (103.4 ng/mL or 248.8 nM 2 hours postdose, and 68.21 ng/g or 164.4 nM 0.5 hour postdose, respectively), which is consistent with other published preclinical and clinical data supporting the role of bimatoprost acid for lowering IOP 11,35,36. ISV-215 formulation also increased bimatoprost levels in the AH and ICB (26.57 ng/mL or 64.02 nM and 65.05 ng/mL or 156.8 nM 0.5 hour postdose, respectively), reaching reported EC 50 values for human ciliary smooth-muscle cells, compared to results with just bimatoprost 0.03% alone.…”
Section: Discussionsupporting
confidence: 92%
“…A possibility of an applied outcome from this research also looms in the horizon. Continued research in PG analogs beyond their original discovery in the iris [13] led to their development as effective IOP reducing topical medications like latanoprost and travoprost [53]. Lowering IOP by increasing the outflow via the conventional pathway will be close to normal physiology [54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…4 A long period of continued research in PG analogs resulted in the development of topical glaucoma medications (such as latanoprost and travoprost) that are among the most effective IOP reducing medications used in the treatment of glaucoma. 21 The effect of other classes of lipids on IOP or outflow facility has not been well studied. Using controlled rodent experiments, it has been shown that increasing dietary omega-3 can reduce IOP due to increased outflow facility.…”
Section: Discussionmentioning
confidence: 99%